Development of Mangrove Ecotourism Based on the Tourist Perspective in Lembung Village, Indonesia - FARID, Akhmad; ARISANDI, Apri; FARIDY, Akhmad Farhan; PRIYANTO, Moh. Wahyudi (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.14.2(66).12, 2023)
Ecotourism development can be carried out using the Importance Performance Analysis (IPA) method. The community perception of ecotourism is very important in its development with the hope that involvement in the management will increase business opportunities and income. Furthermore, the community can preserve local arts and culture, as well as reduce the destruction of mangrove forest areas. The perception of tourism objects is very important in developing the Lembung Mangrove Ecotourism, especially the improvement of infrastructures such as suspension bridges and cleaning facilities. The recommendations for development strategies include (1) completing the supporting infrastructure for natural tourism activities, such as roads, bridges, cleaning facilities, and others. (2) carrying out intensive promotions (3) making special policies in the development of ecotourism, (4) synergizing with traditional arts and culture, as well as (5) empowering local communities in its activities. The Lembung Mangrove Ecotourism has a good natural potential as a tourist destination, and the availability of a fairly dense mangrove forest is the main factor for visit to this place. Therefore, this study aims to analyze the level of tourists' satisfaction using the Importance Performance Analysis (IPA) method, and to determine the Lembung Mangrove Ecotourism Development Strategy.